Kinetics of Physiological Parameters in Response to a Gradually Increasing Speed of Running in Amateur and Professional Runners - Fanis A. Mavliev; Viktor A. Demidov; Viktoriya V. Demidova (Northern (Arctic) Federal University, 2024)
Physical load often varies in the course of one's sports activity, which entails constant multidirectional changes in physiological parameters. The purpose of this paper was to study the kinetics of the chronotropic and inotropic responses of the heart to a gradually increasing load in amateur and professional runners. Materials and methods. Male amateur (n = 25) and professional long- and middle-distance runners (n = 29) with the sports ranks from Candidate for Master of Sport to International Master of Sport were examined. The protocol consisted of an exercise test with a gradually increasing load to failure on a Cosmos Quasar treadmill (Quasar Med, Germany); during the first 2 minutes, the speed gradually increased from 0 to 7 km/h, thereafter, it was gradually increasing by 1 km/h per minute. The treadmill's angle of inclination was 1° throughout the test. Using the Metalyzer 3B software (Cortex, Germany) algorithms, haemodynamic parameters were calculated: cardiac output, stroke volume, and heart rate. Results. In both groups, stroke volume stops increasing by the 4th minute (running speed 9 km/h); during this process, amateurs' heart rate is higher (133 ± 24 beats/min) than that of professionals (123 ± 24 beats/min; p < 0.05). No differences in the kinetics of chrono- and inotropic responses of the heart to a gradually increasing load were observed between the groups. Thus, the load that was used during the exercise test leads to the same kinetics of chronotropic and inotropic responses of the heart to a gradually increasing physical load irrespective of the subjects' training level.